Combination of Salt and Rice Ratio on The Nutritional and Microbiological Qualities of Ronto, a Shrimp Fermented Product from Kalimantan, Indonesia - Rita Khairina; Nooryantini Nooryantini; Susana Ristiarini; Iryanti Fatyasari Nata (International Journal of Advance Tropical Food, 2021)
Ronto is a fermented product of lactic acid bacteria made from rebon shrimp, salt, and rice. This product is a traditional food in the form of side dishes, chili sauce, and flavoring in the coastal communities of South Kalimantan, Indonesia. This research has been conducted on the combination of salt and rice to enhance the quality of shrimp fermentation products. Various studies have reported that salt in the process of shrimp fermentation affect the product quality. However, the impact from combination of salt and rice in various concentrations to the quality of shrimp fermentation products was not yet known. The purpose of this research was to study the effect of the combination of salt and rice on the quality of shrimp fermented products. The experimental was designed with a Completely Randomized Design Pattern, two factors salt and rice. The three concentrations of salt (10%, 11%, and 12%) and two concentrations of rice (20%, 30%,). The results showed that the concentration of salt and rice was significantly influencing on pH, total volatile bases (TVB-N), water content, ash, and microbiological properties. The condition for the best quality result is a combination of 11% of salt and 30% of rice.